Nanolaminated composite materials: Structure, interface role and applications - Azadmanjiri J.; Berndt C.C.; Wang J.; Kapoor A.; Srivastava V.K. (My University, 2025)
This article is a review on the nanolaminate composite materials from a materials science perspective. In fact, nanolaminate composite materials are a category of two-dimensional nanomaterials in the fields of chemistry, materials science and condensed matter physics. Miniaturization of materials to the nanometer scale is improving remarkably in science and technology. Nanolaminates constitute a unique class of nanomaterials that illustrate fascinating mechanical, physical, chemical and electrical properties and these attributes are increasingly being prospected for promising applications. Nanolaminates can typically be developed using bottom-up techniques that are designed with various stacking series along with layer thicknesses. The particular properties of fabricated nanolaminates can be determined by their arrangements, compositions and thicknesses. The properties can be established during the fabrication process by size control of each coating layer and interfacial chemical reactions between layers. Hence, fundamental understanding of nanoscale layered-engineering during the creation of a nanolaminate structure enables tailoring of the overall performance of these composite materials. This work demonstrates the bottom-up physical and chemical approaches for the fabrication of nanolaminates. The influence of the interface layer in the nanolaminate composite materials is considered from the viewpoint of conferring high performance characteristics. The desirable physical attributes will be pursued by incorporation of dopants and site-engineering techniques on various materials that would improve the nanolaminate properties. The final section concludes with an outlook on future directions in this technological field. © 2016 The Royal Society of Chemistry.